2018
DOI: 10.1037/xhp0000520
|View full text |Cite
|
Sign up to set email alerts
|

Visual search with varying versus consistent attentional templates: Effects on target template establishment, comparison, and guidance.

Abstract: Attentional templates can be represented in visual working memory (VWM) when the target varies from trial-to-trial and can be represented in long-term memory (LTM) when the target is consistent during trial runs. Given that attentional templates can be represented in either VWM or LTM, are there any differences in how these representations impact visual search when targets are consistent compared with varying? The current study tested the consistent template hypothesis, which predicts faster performance with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…However, the idea of a one-slot attentional template is disputed because attentional selectivity for two targets is comparable to a single target, even when the targets are variable (Ansorge, Horstmann, & Carbone, 2005;Beck, Hollingworth, & Luck, 2012;Goldstein & Beck, 2018;Grubert, Carlisle, & Eimer, 2016;Irons, Folk, & Remington, 2012;Kerzel & Witzel, 2019;Roper & Vecera, 2012) (but see Biderman, Biderman, Zivony, & Lamy, 2017).…”
Section: Variable and Fixed Templatesmentioning
confidence: 99%
“…However, the idea of a one-slot attentional template is disputed because attentional selectivity for two targets is comparable to a single target, even when the targets are variable (Ansorge, Horstmann, & Carbone, 2005;Beck, Hollingworth, & Luck, 2012;Goldstein & Beck, 2018;Grubert, Carlisle, & Eimer, 2016;Irons, Folk, & Remington, 2012;Kerzel & Witzel, 2019;Roper & Vecera, 2012) (but see Biderman, Biderman, Zivony, & Lamy, 2017).…”
Section: Variable and Fixed Templatesmentioning
confidence: 99%
“…However, searching for targets that vary (Experiment 1) will likely limit the extent to which a precise target representation is generated. Research has shown that increases in template precision leads to a more efficient visual search (Bravo & Farid, 2009 ; Hout & Goldinger, 2015 ; Malcom & Henderson, 2009 ; Menneer et al, 2009 ; Schmidt & Zelinsky, 2009 ; Goldstein & Beck, 2018 ; Lavelle et al, 2021 ). Therefore, if search for repeated targets facilitates improvements in template precision, one would expect to see faster RTs over the course of target repetitions.…”
Section: Discussionmentioning
confidence: 99%
“…The attentional template is defined by cognitive scientists as an active representation of the search goal that can be held either within visual working memory (e.g., Gunseli et al, 2014 ; Schmidt & Zelinsky, 2017 ), or long term memory (e.g., Cunningham & Wolfe, 2014 ; Goldstein & Beck, 2018 ; Woodman et al, 2013 ), and attention is biased towards search items similar to the attentional template (e.g., Bravo & Farid, 2009 ; Vickery et al, 2005 ). To determine the impact that an attentional template has on search performance, observers are often asked to remember a target cue and then later search through a display where the target and/or distractors may be identical or similar to the cue.…”
Section: Future Directionsmentioning
confidence: 99%